Helicon discharge excited by a planar antenna in bounded volume - Virko, V.F.; Slobodyan, V.M.; Shamrai, K.P.; Virko, Yu.V. (Вопросы атомной науки и техники, 2014)
By direct spatial measurements of wave RF magnetic fields it is confirmed that the density jumps in the helicon discharge with a flat (planar) antenna result from changes in axial modes of standing helicon waves in a limited volume. In independently produced plasma the planar antenna resistance was measured at various plasma densities n and magnetic fields B0. In the studied range of parameters (n/B0 ≤ 2.5×1020 T−1m−3) the planar antenna impedance increases with the ratio n/B0, in contrast to other types of helicon antennas. The resonances of RF power absorption, caused by standing waves excitation, for the planar antenna are observed at about two times higher values of n/B0 than for the frame m = 1 antenna.